Fibromyalgia syndrome in chronic hemodialysis patients is associated with depression, hypoalbuminemia and inflammation - Gürlek Demirci, Bahar; Tutal, Emre; Erkmen, Mehtap; Erdoğan, Elçin; Sezer, Siren (The European Research Journal, 2019)
Objectives: Fibromyalgia syndrome (FMS) is an entity that presents with wide-spread chronic pain in musculoskeletal system, disturbed sleep, reduced mental functioning and depressed mood. We aimed to determine the incidence of FMS in our hemodialysis patients and to evaluate the association between FMS, depression and inflammation in patients ongoing hemodialysis. Methods: Among 169 patients, 140 patients were enrolled into our study. Twenty-nine patients were excluded according to exclusion criteria. Demographic characteristics including age, sex, body mass index, duration of dialysis, the etiology of end stage renal disease, the dialysis adequacy (Kt/V) were also recorded. All patients were evaluated through 2010 ACR preliminary diagnostic criteria including widespread pain index (WPI) and total symptom severity. All subjects completed Beck depression inventory (BDI) to determine psychological status. Results: Among 140 hemodialysis patients, 76 (54.2%) patients presented chronic widespread pain and 20 patients (14.2%) met the 2010 ACR criteria for FMS. Patients were divided into FMS (n = 20; 14.2%) and non-FMS (n = 120; 85.8%) groups. FMS group had significantly higher serum C-reactive protein levels and lower serum albumin levels when compared to non-FMS group. BDI (31.4 ± 1.4 vs 14.8 ± 0.6, p < 0.005), WPI (11.2 ± 0.7 vs 2.8± 0.2, p = 0.002) and symptom severity (7.3 ± 0.3 vs 3.7 ± 0.1, p < 0.005) scores were significantly higher in FMS group. Conclusions: The FMS itself and the related symptoms were correlated with depression in maintenance hemodialysis patients. Besides, inflammation and perhaps malnutrition-inflammation sydrome may trigger FMS in this population.